A Study On Quaternionic \(B_2\)-Slant Helix In Semi-Euclidean 4-Space - Babadağ, Faik (Journal of Informatics and Mathematical Sciences, 2016)
In this work, we defined a quaternionic \(B_2\)-slant helix in semi-Euclidean space \(E_2^4\). Then we gave Frenet formulae for the quaternionic curve in semi-Euclidean space \(E_2^4\). Also, we investigated some necessary and sufficient conditions for a space curve to be a quaternionic \(B_2\)-slant helix according to quaternionic curves in semi-Euclidean space \(E_2^4\).